Hybrid driver concept for powering the ornithopters - (:unkn) unknown (American Institute of Aeronautics and Astronautics Inc., 2009)
Birds and insects move relatively bulky wings respect to their size at high frequencies to stay in the air and precisely control their flight with very intricate adjustments. Insects are known to manage their power and precision by using power and control muscles. In this paper, use of the DC and piezo motor combination is proposed to benefit from the high torque of DC motors, energy storing ability of a flywheel, and precise motion of piezo motors to obtain excellent flying power, gliding capability and performing precise moves efficiently. The proposed design flaps the wings by using a DC motor. Two piezo motors are proposed to control the gliding and precise maneuvers by small wing motions. The forces created by the wing motions and forces at the pins are experimentally obtained and study indicated that the specs of the commercially available piezo motors are at the borderline of moving the two structural pins to realize the proposed design. Copyright © 2009 by the American Institute of Aeronautics and Astronautics, Inc.